Effect of morphological ordering on the electrochemical performance of MnO2-Graphene oxide composite. (10th September 2019) - Saha, Samik; Maji, Prasenjit; Pethsangave, Dattatray A.; Roy, Atanu; Ray, Apurba; Some, Surajit; Das, Sachindranath
Abstract: In this paper, we compared the electrochemical performances of ordered MnO2 -Graphene (MnO2 -GO) oxide with the disordered system of the same composite. The ordered system is fabricated using electrospinning while the disordered system is fabricated dropcasting the same precursor under similar synthesis condition. This fiber-like ordered structure exhibits excellent electrochemical properties both in terms of specific capacitance and cyclic stability because of excellent connectivity between the individual nanoparticles. The electrospun sample having MnO2 : GO = 5:2 (by weight) demonstrates the highest specific capacitance of 892.8 F g −1 whereas the disordered sample having same ratio of MnO2 and GO demonstrates 546.9 F g −1 at 2 mV s −1 . To correlate the superior electrochemical performance of the ordered sample compared to the disordered one, room temperature dielectric measurements are performed which reveals various parameters like conductivity; diffusivity and mobility of charge carriers. An asymmetric supercapacitor device is fabricated using the fiber-like ordered structure as an active electrode. The device offers maximum power density of 2.8 kW kg −1 and maximum energy density of 96.75 Wh kg −1 with a 93.3% retention after 5000 GCD cycles. Graphical abstract: Image 1 Highlights: Ordered and disordered systems of MnO2 -GO composite have been fabricated. Ordered electrospun sample offers better conductivity and storage capacity. Dielectric measurement has been used to evaluate different parameters. Two electrode device performance is demonstrated.